1982
DOI: 10.1289/ehp.8246207
|View full text |Cite
|
Sign up to set email alerts
|

Presence, introduction and removal of mutagenic activity during the preparation of drinking water in the Netherlands.

Abstract: A survey of the presence of mutagenic activity in drinking water of 18 cities in the Netherlands revealed that in drinking water of 13 cities mutagenic activity could be demonstrated. The activity was detected in the Ames test after concentrating the organic mutagens with a XAD-4/8 procedure. Dose-related responses were observed with concentrates corresponding to 0.5 to 3.0 liters of drinking water. A study of the changes in mutagenic activity during the preparation of drinking water in a few waterworks showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Water extracts are too complex to carry out successful qualitative analyses of mutagens, and some form of separation/fractionation is required. In studies where mutagens in neutral drinking water extracts have been fractionated, the original activity has been distributed among several subfractions, and further fractionation has suffered from difficulties in detecting the diluted activity (21)(22)(23). However, Meier et al (24) found that when the muta-genicity of the extract of strong acids, obtained from an aqueous solution of chlorinated humic acids was fractionated by C18 column HPLC, the activity was concentrated in two distinct subfractions: the fraction collected in the middle of the chromatographic run being twice as active as the fraction which eluted later.…”
Section: Discussionmentioning
confidence: 99%
“…Water extracts are too complex to carry out successful qualitative analyses of mutagens, and some form of separation/fractionation is required. In studies where mutagens in neutral drinking water extracts have been fractionated, the original activity has been distributed among several subfractions, and further fractionation has suffered from difficulties in detecting the diluted activity (21)(22)(23). However, Meier et al (24) found that when the muta-genicity of the extract of strong acids, obtained from an aqueous solution of chlorinated humic acids was fractionated by C18 column HPLC, the activity was concentrated in two distinct subfractions: the fraction collected in the middle of the chromatographic run being twice as active as the fraction which eluted later.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, surrogate mixtures of nonvolatile mutagens have been obtained by chlorination of humic substances (4,6,(12)(13)(14)(15). Such mixtures have been examined for short-term and long-term toxicological effects and by the use of short-term bioassays in conjunction with chemical fractionation for compound identification (17)(18)(19)(20). We have developed a general preparative procedure for the isolation (21), separation (IT), and chemical characterization (22) of mutagenic components from drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…It must be taken as established that treating drinking water with disinfectants produces compounds that have mutagenic activity. Whether disinfectants other than chlorine produce the same levels of mutagenic chemicals as chlorination is likely to depend considerably on local water conditions as demonstrated by Dutch researchers (34,39). Much of the mutagenic activity found in drinking water appears to result from the reaction of chlorine with naturally occurring organic material in the source water.…”
Section: Discussionmentioning
confidence: 99%
“…Technol., Vol. (34,39). In Holland, indirect-acting chemicals present in the source water were destroyed by chlorination, and in their place there was a consistent increase in mutagens that act directly in Salmonella strains TA98 and TA100.…”
Section: Toxicology Of By-productsmentioning
confidence: 99%